Analisis Six Big Loss Pada Mesin Pengolahan Minyak CPO dengan Metode OEE (Studi Kasus: di PT. Fajar Baizury and Brother) - Saputra, Arie; Muzakir, Muzakir; Suryani, Munti (Universitas Teuku Umar, 2020)
This study discusses determining each CPO oil processing machine in the production process using the Overall Equipment Effectiveness method, determining the percentage of each factor contained in the six major losses and determining the dominant factors needed in the CPO oil processing machine. Based on the results of the study showed that the OEE value of each of the CPO oil processing machines OEE value on the strelelizer was 71.41%, for the Thesher / Thickening machine at 75.64%, for the Screw Press machine at 68.21 and OEE value on the clarification machine is 78.16% while the six major loss factor has the greatest proportion of time loss and needs to be repaired is reducing the speed of loss that is equal to 84.62%, this condition shows the ability of the press and clarification machine in achieving the target production and in achieving the ideal conditions that is yaitu85%. Percentage of the magnitude of the factors contained in the six major losses, namely the strelelizer machine due to the Process of Disability Losses and Yield Reduction with the same percentage level that is equal to 49.03%, on the Threser machine caused by Reduction of Speed Loss with a percentage level of 72.70%, on Press machines Generated by Reduced Speed Loss with a percentage level of 34.50% and Clarification machines caused by Reduced Speed Loss with a percentage level of 84.62%, from the four CPO processing machines a factor of six large losses that is, on a disadvantage machine, this is difficult to avoid because of this deficiency also because of the poor quality of CPO oil due to free fatty acid levels and high water content. The dominant factor influencing the effectiveness of the use of CPO oil processing machines that occurred during the period August 2018-July 2019 with the OEE method on the Screw Press machine that is equal to 73.85% as expected based on world class OEE standards (85%) using with other machines this is caused by the speed and pressure when processing FFB is reduced / unstable, the press machine that is used often to repair the damage produced does not meet the expected quality and quantity specifications.